Karakteristik Minyak Jelantah Hasil dari Proses Pemurnian dengan Ampas Tebu pada berbagai Variasi Suhu dan Waktu Pengadukan - Hakim, Rian; Wrasiati, Luh Putu; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): DesemberDO - 10.24843/JRMA.2021.v09.i04.p01, 2021)
Used cooking oil is cooking oil that has been used over and over again. Used cooking oil can be used as raw material for soap and biodiesel. However, before being used, the used cooking oil must be purified using an adsorbent. This study aims to determine the effect temperature and stirring time on the characteristics of used cooking oil purified with bagasse and determine the best temperature and stirring time to produce the best characteristics of used cooking oil. This study used a factorial randomized block design. The first factor was the adsorption temperature which consists of 70 °C, 80 °C, 90 °C, and 100 °C. The second factor was the stirring time which consists of 3 levels, namely: 60, 70, and 80 minutes. The data were analyzed by analysis of variance and continued with the Tukey test. The results showed that the adsorption temperature and stirring time significantly affected the clarity, water content, free fatty acid content, and brightness level. The interaction between treatments had a very significant effect on the level of clarity and brightness. The best treatment of the used cooking oil refining process using bagasse is the treatment at 100°C temperature and 80 minutes stirring time, with the characteristics of a clarity level of 0.149±0.010 A, 0.13±0.02% water content, 0.21±free fatty acid content. 0.02% and a brightness level of 47.37±0.01L*. Keywords : Used cooking oil, temperature, stirring time, sugarcane bagasse.